Large resistivity in numerical simulations of radially self-similar outflows - Čemeljić, M.; Vlahakis, N.; Tsinganos, K. (2014)
We investigate the differences between an outflow in a highly resistive accretion disc corona, and the results with smaller or vanishing resistivity. For the first time, we determine conditions at the base of a two-dimensional radially self-similar outflow in the regime of very large resistivity. We performed simulations using the PLUTO magnetohydrodynamics (MHD) code, and found three modes of solutions. The first mode, with small resistivity, is similar to the ideal-MHD solutions. In the second mode, with larger resistivity, the geometry of the magnetic field changes, with a `bulge' above the superfast critical surface. At even larger resistivities, the third mode of solutions sets in, in which the magnetic field is no longer collimated, but is pressed towards the disc. This third mode is also the final one: it does not change with further increase of resistivity. These modes describe topological change in a magnetic field above the accretion disc because of the uniform, constant Ohmic resistivity.
Keywords: Astrophysics - Solar and Stellar Astrophysics; ISM: jets and outflows; magnetic fields; MHD; stars: pre-main-sequence